Zine “Satu Darah Juang” as an artistic practice to reconstruct Ambon family memories: a practice-led research approach - Akyuwen, Ardiles; Bima Wicaksana, Inovensius Hugo; Tanrere, Rezki Gautama (Gelar: Jurnal Seni Budaya, 2025)
“Satu Darah Juang” is a photography zine work produced through artistic practice based on research, or commonly called practice-led research, which explores religious and cultural values in the family of Petrus Mailoa (the author's grandfather), who lives in Ambon City, Maluku. Based on a collection of family photo archives, this zine reconstructs collective memory and local spirituality through a process of selecting photo archives, recalling conversations with Opa Petu, Oma Bo, Mama Nel, Aunt Poppy, and Aunt Noor, sequencing stages, digital collage, to creating illustrations analogously. This process produces a photo narrative that is effective, visual, and historical, and creates a dialogue between the personal realm and communal culture. The practice-led approach functions to integrate visual experience with the concept of visual communication (the concept of punctum Barthes), cultural psychoanalysis (Freud & Lacan), and visual anthropology. This work is a visual artifact, has the function of being a medium for introspection, a space for dialogue between the private and the public, and then becomes a form of expression beyond the limitations of conventional documentary photography. “Satu Darah Juang” has gone through exhibition curation and audience interaction; this process is the answer that there is potential for cultural communication and social reflection. Therefore, this research provides a clear affirmation of the position of art practice as a valid research method to record, transform, and then inherit cultural values through an interdisciplinary approach.